The issues of short circuit in housing development in Malaysia: Focusing in Perak / Muhammad Faris Abdul Jalil - Abdul Jalil, Muhammad Faris (2016)
Most of talk in this thesis report is research about the Issue of Short Circuit in Perak Housing. This research is begin by the cases of short circuit happen in many old housing that focusing on wiring maintenance. This short circuit will be carry out the successfully of the objective by make a questionnaire and validation data on the officer that has knowledge and experience on this topic. All in this report must be containing into the aim of objective to make the body report is still in the topic research. The flow of this report is elaborate about the causes, impact and solution of short circuit happen. Before that it will be show the introduction about the wiring, electrical and services that have in building, specifically on housing to make the reading more understanding the source wiring. By that intro, the research will go through focusing into the aim of this research. Where it will talk about the analysis of this research at three placed that represent to another district of this Perak. After the analysis is done, the data will be finding to filtered by choose the answer of objective.